Management of Type 2 Diabetes Mellitus with Complications and Hypertension in a 62 Year Old Male Patient : A Family Medicine Approach - Andarini, Sri; Bobby Christian, Samuel (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Type 2 Diabetes Mellitus (T2DM) and Hypertension are chronic diseases with complex risk factors requiring comprehensive management. A holistic family medicine approach is crucial for addressing biomedical, psychological, and socio-economic aspects. Objective: This case report aims to describe the holistic management of a 62-year-old male patient with uncontrolled T2DM with complications, primary hypertension, and cutaneous candidiasis using a family medicine approach. Method: This is a case report study. Data were collected through autoanamnesis, physical examinations, and home visits. A holistic diagnosis was established using the five-axis model. Family assessment was conducted using a genogram, APGAR, and SCREEM tools. Risk factors were visualized using the Mandala of Health. Interventions were patient-centered, family-focused, and community-oriented. Results: The patient was diagnosed with T2DM with peripheral circulatory complications, primary hypertension, and candidiasis intertriginosa. Multiple internal and external risk factors were identified, including genetics, obesity, diet, smoking, sedentary lifestyle, poor sleep patterns, personal hygiene, and physical environment. Comprehensive intervention resulted in improved clinical parameters, with random blood glucose decreasing from >600 mg/dL to 189 mg/dL and blood pressure improving from 145/76 mmHg to 128/85 mmHg. Conclusion: A comprehensive family medicine approach effectively improved clinical outcomes and self-management in a complex case with multiple comorbidities.